Prosedur Pengangkatan Anak di Pengadilan Negeri Oelamasi (Studi Kasus Penetapan No 5/Pdt.P/2023/PN Olm) - Nur Fadhilah; Siti Ramlah Usman; Husni Kusuma Dinata (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The purpose of this research is to find out the procedure of child adoption at the Oelamasi District Court and the judge's reasoning in granting the application for child adoption with prospective parents over 55 years old. The research method used is empirical research. The results showed (1) The child adoption procedure at the Oelamasi District Court is in accordance with the child adoption arrangements contained in the laws and regulations. Particularly in this case, the child who was adopted was not under the care of a social organization but under the care of the prospective adoptive parents. In addition, in this case the prospective adoptive parents did not fulfill one of the requirements for child adoption contained in Article 13 of the Government Regulation, which in turn is the authority of the judge in accepting or rejecting the application. (2) The judge's reasoning in granting the application for child adoption in Stipulation Number 5/Pdt.P/2023/PN Olm is by referring to the provisions of Article 28 B paragraphs (1) and (2) jo Article 28 D paragraph (1) of the 1945 Constitution of the Republic of Indonesia which prioritizes the principles of justice and the best interests of the child so that even though the age of the Plaintiffs no longer meets the requirements of the legislation because they are more than 55 (fifty five) years old does not have to hinder the noble intentions of the Plaintiffs to adopt a child.